BENTUK TINDAK PIDANA KORUPSI DI SEKTOR BARANG DAN JASA DALAM PERSPEKTIF HUKUM EKONOMI - Sri Agustini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Procurement of goods and services is not only limited to the selection of project partners with the purchasing department or the official two-party agreement, but covers the entire process from the start of planning, preparation, licensing, determination of tender winners to the implementation and administrative processes in procurement of goods, work or services such as technical consulting services, financial consulting services, legal consulting services or other services. Article 33 Paragraph (4) of the 1945 Constitution states: